2012
DOI: 10.4103/0377-4929.101733
|View full text |Cite
|
Sign up to set email alerts
|

Critical histopathological analysis of 25 dedifferentiated liposarcomas, including uncommon variants, reviewed at a Tertiary Cancer Referral Center

Abstract: This study forms the largest documentation of DDLSs, including its wide histopathological spectrum, from our country. Rare cases overlap with pleomorphic liposarcoma. S100-P and MDM2 are useful in substantiating adipocytic differentiation, especially in selected cases. Analysis of adequate tumor sections is vital for correct identification of a DDLS. Surgical excision with adjuvant RT forms optimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Chromosomal analysis of 12q15 amplification, which yields positive results in 90 % of cases of WDLS/DDLS, 17,18 was performed on eight percutaneous biopsy specimens as part of the pathologic examination. Seven had positive results for 12q15 amplification (sensitivity for WDLS/DDLS detection, 87.5 %); all eight specimens, including the case with negative results for 12q15 amplification, were diagnosed as either WDLS or DDLS (the patient with negative results for 12q15 had a history of recurrent WDLS).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal analysis of 12q15 amplification, which yields positive results in 90 % of cases of WDLS/DDLS, 17,18 was performed on eight percutaneous biopsy specimens as part of the pathologic examination. Seven had positive results for 12q15 amplification (sensitivity for WDLS/DDLS detection, 87.5 %); all eight specimens, including the case with negative results for 12q15 amplification, were diagnosed as either WDLS or DDLS (the patient with negative results for 12q15 had a history of recurrent WDLS).…”
Section: Resultsmentioning
confidence: 99%
“…A Critical histopathological analysis of dedifferentiated liposarcomas revealed that CD34 was negative in 9/11 cases; negative rate of s-100 was 92% (23/25); MDM2 was diffusely positive in well-differentiated areas and focally in dedifferentiated areas in the tumor with homologous dedifferentiation; SMA was positive in 2/8 tumors (24). Andrei et al proved that MDM2 and CDK4 were significative markers for confirming the diagnosis of well-differentiated liposarcoma (23).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, differentiated sarcoma can be subdivided into five main subtype: Resembling pleomorphic malignant fibrous histiocytoma, fibrosarcoma, rhabdmyofibrosarcoma, myxofibrosarcoma and hemangiopericytoma (25,26). A total of 76% of dedifferentiated liposarcomas was high-grade (24).…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation in LPS is defined as 'nonlipogenic' tumor area occupying at least one low power (10x) in proximity of well-differentiated LPS (WDLS). 52 A wide spectrum of histological diverse components can be identified in the dedifferentiated LPS which pose considerable diagnostic challenge even in excised specimens. The initial smaller or incisional biopsy may be not be representative and may contain either differentiated liposarcomatous component or dedifferentiated component alone.…”
Section: Liposarcomamentioning
confidence: 99%
“…Four major types of dedifferentiation can be encountered in LPS. 52 In smaller biopsy tumor may be misdiagnosed according to dedifferentiated components such as rhabdomyosarcoma, follicular dendritic cell sarcoma, GIST or sometimes diagnosis may completely missed due to lack of representation. Immunohistochemistry can be of use for correct diagnosis of dedifferentiation in LPS, however, interpretation has to be made with caution.…”
Section: Liposarcomamentioning
confidence: 99%